Management information system in Nigerian secondary schools: challenges and way forward - Yusuf, Suleiman; Ayoku, Oba Baba; Funmilayo, Ibrahim Bashirat (International Journal of Educational Innovation and Research, 2022)
Information is regarded as a fundamental resource to an organization and as such its management is apparently one of the most strategic operational instruments for organizational efficacy. Management information system plays an indispensable role in the smooth running of secondary schools. This paper examined the management information system in Nigerian secondary schools. The concept of a management information system was examined from different perspectives. Also, the features, components and development of management information systems in Nigeria were examined. The national policy on ICT integration in the Nigerian school system, the roles of MIS, challenges and strategies for effective integration of information systems in the Nigerian school system were elucidated consecutively. The study concluded that the school system requires an efficient management information system to take the secondary school a step further and boosts students’ academic success. It was recommended among others that secondary school administrators must maximally integrate educational management information system towards making an appropriate decision, seminars, conferences and workshops on educational management information system should be periodically organized for relevant stakeholders in secondary education and intensive efforts should be made by stakeholders (e.g. government, NGO, philanthropists) in secondary education towards genuine integration of ICT policies in the school.